A digital panorama mapping system with soft-IMU technology: experience with a Chinese low-cost mobile mapping system. Issue 348 (3rd May 2016) - Xu, Z.; Li, L.; Xiang, Z.; Long, C.
Abstract : Mobile mapping systems (MMSs) provide capability for direct geo-referencing, and rapid and convenient acquisition of geographic data elements. Combining global positioning system/inertial measurement unit/distance measurement indicator (GPS/IMU/DMI) data is one of the most attractive methodologies for such systems. Inertial measurement unit data give attitude information, but the equipment is expensive and faces technological blockade by foreign companies. To overcome this limitation, the current paper explores a soft-IMU technique based on panorama vision, which can acquire more information from the environment because of its wide instantaneous field of view (IFOV) compared with traditional cameras. The proposed soft-IMU technology automatically extracts and tracks image registration points (IRPs) in panorama data, and corrects paths using correction points. The development history of the mobile mapping system, the software and hardware configuration of our prototype digital panorama mapping DPM™ products, the system calibration model principle and object measurement are described. Finally, it is demonstrated that the system precision meets the demands of daily data acquisition in field experimental studies.